(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This is a systematic review of studies made between 1960 and 2018 about analytical-behavioral interventions for patients diagnosed with schizophrenia at PsycINFO, PubMed, Lilacs, Pepsic, BDTD, REBAC, Comportamento em Foco and SCC. After applying the inclusion and exclusion criteria, 45 studies were selected. It was found that there was a decrease in the number of foreign publications after the 1980s and an increase in unpublished national studies. Interventions generally focused only one class of target responses. Few studies reviewed performed training of behavioral agents, planned and evaluated generalization and/or carried out follow-up measures. It was found that the most recent studies tested control variables and performed interventions outside psychiatric hospitals. The use of coercive contingencies and the exclusive use of tangible consequences decreased while the use of social consequences increased. The behavioral-analytical procedures employed were generally successful, but it was not possible to pinpoint which one was more effective.